International Symposium on Distributed Computing and Artificial Intelligence 2008 (DCAI´08) - Corchado Rodríguez, Juan Manuel; Rodriguez, Sara; Llinas, James; Molina, Jose M. (Advances in Intelligent and Soft Computing,, 2009)
The International Symposium on Distributed Computing and Artificial Intelligence is an annual forum that brings together ideas, projects, lessons, etc. associated with distributed computing, artificial intelligence and its applications in different themes. This meeting has been held at the University of Salamanca from the 22th to the 24th of October 2008. The technology transfer in this field is still a challenge and for that reason this type of contributions has been specially considered in this edition. This conference is the forum in which to present application of innovative techniques to complex problems. The artificial intelligence is changing our society. Its application in distributed environments, such as the Internet, electronic commerce, mobile communications, wireless devices, distributed computing, and so on is increasing and is becoming an element of high added value and economic potential, both industrial and research. These technologies are changing constantly as a result of the large research and technical effort being undertaken in both universities and businesses. The exchange of ideas between scientists and technicians from both academic and business areas is essential to facilitate the development of systems that meet the demands of today's society. This symposium has evolved from the Iberoamerican Symposium on Distributed Computing and continues to grow and prosper in its role as one of the premier conferences devoted to the quickly changing landscape of distributed computing, artificial intelligence and the application of AI to distributed systems. This year's technical program is extremely strong and diverse, with contributions in both established and evolving areas of research. Submitted papers came from over 16 different countries, representing a truly "wide area network" of research activity. The DCAI technical program includes 88 papers (74 long papers, 12 short papers and 2 doctoral consortium) selected from a submission pool of 142 papers, from 16 different countries.